A qualitative exploration of nurse's perception of Critical Outreach Service: A before and after study - Athifa, M.; Finn, J.; Brearley, L.; Williams, Teresa; Hay, B.; Laurie, K.; Leen, T.; O'Brien, K.; Stuart, M.; Watt, M.; Leslie, Gavin (Elsevier Inc, 2011)
Summary:Background: Critical Care Outreach Services (CCOS) have been reported to streamlinethe transfer of patients from the intensive care unit (ICU) to the wards and providea follow-up service supporting ward staff to provide optimum care for patientsdischarged from ICU.Purpose: The aim of this study was to explore the perceptions of nursing staff beforeand after the introduction of a CCOS at three adult teaching hospitals in Perth,WesternAustralia.Methods: Exploratory focus groups were conducted with registered nurses (RNs)at each of the participating hospitals prior to and 6 months after the introductionof a CCOS. Framework analysis was used to analyse the transcribed datausing a thematic approach with themes developed from the narratives of theparticipants.Results: Inexperienced RNs in particular voiced positive comments about the CCOS.The role was seen as a senior nurse who was an additional resource for less experiencedstaff as they educated them on complex procedures that were not common on thegeneral wards. The RNs reported that apprehensions about the role that they hadpre-implementation were not borne out in practice and that they believed that theCCOS had positive effects on patient outcomes.Conclusion: The CCOS improved communication processes between members ofthe multidisciplinary team and units within the hospital, which subsequentlyenhanced the ward transition process for critically ill patients and ward nursingstaff.